Vapor-Liquid Equilibrium at Several Experimental Conditions of the Binary Mixtures Methyl Lactate with n-Alkanols - Lafuente, Carlos; Ezquerra, Rubén; Latorre, Alberto; Mahdoui, Najla Ben (Journal of Applied Solution Chemistry and Modeling, 2018)
In this contribution the vapor-liquid equilibrium of the binary mixtures formed by methyl lactate and the first four lineal alkanols has been determined at constant pressure (p = 101.325 kPa) and at constant temperature (T = 323.15 K). The results have been adequately correlated with the Wilson equation. The obtained data have been satisfactorily checked for thermodynamic consistency using the van Ness method. Furthermore, we have applied the UNIFAC method to predict the vapor-liquid equilibrium and compared these predictions with the experimental results.